Factors Affecting Interest in E-Money Users Via Digital Based Payment Applications Among Accounting Students of Universitas Kristen Satya Wacana - Pongratte, Meyske Triananda; Nugroho, Paskah Ika (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2023)
This research aims to identify and analyze factors that influence interest in using e-money through digital-based payment applications among students majoring in Accounting at Universitas Kristen Satya Wacana. E-money has become an integral part of the digital transformation in the world of finance, and understanding the factors that influence users' interest in this technology has significant relevance. This research uses a framework that includes variables such as perceived benefits, perceived risks, security, trust, and demographic factors such as gender. The questionnaire survey method was used to collect data from a sample of students. The results of data analysis show that the perceived benefit factor has a positive and significant influence on interest in using e-money, while the perceived risk, security, trust and gender factors do not have a significant influence. This research provides insight into the preferences and factors that influence Accounting students' interest in adopting e-money, with implications for the development of e-money technology and relevant marketing strategies.